The digital maturity of the Russian metallurgical industry: drivers and growth challenges in the new geopolitical environment. Part I. Assessment of the innovation potential of digital transformation - I. S. Prokhorova; V. S. Ustinov; A. V. Elkhova (Вестник университета, 2023)
The article examines the problems on implementing the strategy of digital transformation of industries in the Russian economy based on the metallurgical industry that determines the economic growth opportunities of the three industrial sectors which form the largest part of gross domestic income. The subject of the study is the level of digital maturity of metallurgical companies under economic sanctions. The purpose of the study is to determine the current level of digitalisation of metallurgical companies and to form the directions for possible development of digital technologies in the context of anti-Russian sanctions. The methodology of the study is based on system, indicative, comparative and statistical methods of analysis. The first part of the study is devoted to a comprehensive assessment of the industry’s digital maturity and identification of key trends in business digitalisation to characterise its innovation potential as a major resource provider in the Russian industry. A system of indicators for assessing digital maturity based on variable methodologies is considered a criterion for assessing innovation potential of digital business transformation. The results of the analysis show that the metallurgy complex has sufficient growth potential for business digital maturity and refers to the drivers of digitalisation.